Relevant essential oil components: a minireview on increasing applications and potential toxicity. (13th October 2021) - Fuentes, Cristina; Fuentes, Ana; Barat, José Manuel; Ruiz, María José
Abstract: Phenolic compounds carvacrol, thymol, eugenol, and vanillin are four of the most thoroughly investigated essential oil components given their relevant biological properties. These compounds are generally considered safe for consumption and have been used in a wide range of food and non-food applications. Significant biological properties, including antimicrobial, antioxidant, analgesic, anti-inflammatory, anti-mutagenic, or anti-carcinogenic activity, have been described for these components. They are versatile molecules with wide-ranging potential applications whose use may substantially increase in forthcoming years. However, some in vitro and in vivo studies, and several case reports, have indicated that carvacrol, thymol, and eugenol may have potential toxicological effects. Oxidative stress has been described as the main mechanism underlying their cytotoxic behavior, and mutagenic and genotoxic effects have been occasionally observed. In vivo studies show adverse effects after acute and prolonged carvacrol and thymol exposure in mice, rats, and rabbits, and eugenol has caused pulmonary and renal damage in exposed frogs. In humans, exposure to these three compounds may cause different adverse reactions, including skin irritation, inflammation, ulcer formation, dermatitis, or slow healing. Toxicological vanillin effects have been less reported, although reduced cell viability after exposure to high concentrations has been described. In this context, the possible risks deriving from increased exposure to these components for human health and the environment should be thoroughly revised. Graphical Abstract: UF0001